2019
DOI: 10.1002/acm2.12657
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of cervical cancer with electronic brachytherapy

Abstract: Purpose We report the first cervical cancer cases treated with interstitial electronic brachytherapy (eBT) at our hospital and compare them with plans made with high‐dose‐rate interstitial brachytherapy based on Ir192 (HDR‐BT). Materials and methods Eight patients with cervical cancer were treated with the Axxent eBT device (Xoft, Inc.). Planning was with magnetic resonance imaging and computed tomography following the recommendations of the EMBRACE protocol. The dosimetry parameters of organs at risk (OAR) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…The Xoft System [ Figure 1 ] is FDA-approved, CE marked and is licensed in a growing number of countries for the treatment of cancer. [ 26 , 28 , 38 ]…”
Section: Methodsmentioning
confidence: 99%
“…The Xoft System [ Figure 1 ] is FDA-approved, CE marked and is licensed in a growing number of countries for the treatment of cancer. [ 26 , 28 , 38 ]…”
Section: Methodsmentioning
confidence: 99%
“…Although the clinical implications of the hot spots remain unknown, they represented a cause for concern in the extent and viability of clinical trials needed to evaluate the approach. In a previous study in which cervical cancer patients were treated with intracavitary applicators using the Xoft Axxent electronic brachytherapy source it was found that hot spots to normal tissue increased slightly relative to what would have been delivered with 192 Ir for 8 patients (V 150% was 132% vs 124% on average and V 200% was 67% vs 63% on average), and no increase in acute mucositis was observed 36 …”
Section: Discussionmentioning
confidence: 93%
“…In a previous study in which cervical cancer patients were treated with intracavitary applicators using the Xoft Axxent electronic brachytherapy source it was found that hot spots to normal tissue increased slightly relative to what would have been delivered with 192 Ir for 8 patients (V 150% was 132% vs 124% on average and V 200% was 67% vs 63% on average), and no increase in acute mucositis was observed. 36 Another approach for improving cervical cancer brachytherapy, direction-modulated brachytherapy (DMBT), is a technically viable and well-investigated. 15,17,18 In a 45-patient treatment planning study it was found that the DMBT applicator with a ring compared to a conventional tandem and ring applicator resulted in a mean (range) organ-at-risk sparing of À4.07% AE 9.90% (À45.3%, 10.4%) for bladder, 3.17% AE 4.57% (À26.5%, 6.1%) for rectum, and À3.63% AE 4.49% (À18.3%, 3.9%) for the sigmoid colon when 192 Ir was used as the radiation source.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, EBT devices are mobile and may be used in any room that fulfils basic requirements for operating kV-energy emitting X-ray devices (e.g., classical X-ray imaging, C-arm fluoroscopy, or computed tomography – CT) [ 7 , 8 , 9 ]. Current applications of EBT mostly involve intracavitary (intraoperative) radiotherapy of breast, brain, and spine tumors, but also intravaginal or intrauterine EBT and superficial EBT of skin tumors [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Purposementioning
confidence: 99%